PENGGUNAAN METODE KAIDAH USHULIYAH DALAM MEMAHAMI NASH SECARA TEKSTUALIS DAN KONTEKSTUAL - alfian qodri azizi (Journal of Islamic Studies and Humanities, 2020)
AbstractIn essence the product of a Kaidah is an extract from the proposition of the Al- Qur’an and the Hadith which is the main priority source of Islamic law. However, what needs to be an important point is that the use of kaidah cannot be immediately applied to all legal cases equally because this causes one to be trapped in a textualist, partial, and historical dimension of legal understanding. Therefore, this paper would like to examine how the method of understanding textual kaidah ushuliyah ? and How is the application of the kaidah ushuliyah to suit the social context of the community? This research is in the qualitative domain which is more directed towards conceptual leadership based on library analysis. The results of this research are the method of understanding textually kaidah ushuliyyah divided into mutakallimin methods, ahnaf methods, mixed methods. Furthermore, so that the use of the kaidah ushuliyyah can be in accordance with the social context it must be reviewed in accordance with the specificity of the reasons rather than based on the general speech.